Catheter‐related infection rates in patients receiving customized home parenteral nutrition compared with multichamber bags. Issue 1 (6th August 2021) - Crooks, Benjamin; Harrison, Simon; Millward, Graham; Hall, Kirsty; Taylor, Michael; Farrer, Kirstine; Abraham, Arun; Teubner, Antje; Lal, Simon
Abstract: Background: The risk of bloodstream infections may be increased in hospitalized patients receiving ready‐made parenteral nutrition (PN) multichamber bags (MCBs) compared with customized PN; however, as highlighted in recent international guidelines, there are no comparable data relating to home PN (HPN). Methods: Data from a prospectively maintained database were analyzed to compare incidence rates of catheter‐related bloodstream infections (CRBSIs) between patients receiving customized HPN compared with MCB HPN at a national UK referral center between May 2018 and August 2020. Results: Sixty patients with chronic intestinal failure were commenced on MCBs and 45 received customized HPN for a total of 5914 and 7641 catheter days, respectively. No difference in CRBSI incidence was found (0.51/1000 catheter days for MCBs, 0.39/1000 catheter days for customized HPN; incidence rate ratio, 1.29; 95% CI, 0.26–6.37). Eighteen patients were switched from customized HPN to MCB HPN. The study period covered 7401 catheter days receiving customized HPN and 4834 days on MCBs. No significant change was noted in the CRBSI rates following this switch (0.27/1000 catheter days receiving customized HPN vs 0.21/1000 catheter days on MCBs; incidence rate ratio, 1.31; 95% CI, 0.12–14.3). Conclusion: The use of MCBs for HPN patients is not associated with an increased risk of CRBSI. This study will inform international guidelines and provide reassurance for the continued, safe use of MCB HPN.